Response of Superior Maize Verieties to Different Combination of Inorganic and Organic Fertilization - Rusnadi Padjung; Ifayanti Ridwan; Muh. Farid BDR; N. Nasaruddin; Muh. Fuad Anshori (Universitas Sembilanbelas November Kolaka, 2021)
Productivity of superior genotypes often did not satisfyingly achieve its genetic yield potential. Interaction between genetics and environmental factors more likely to driven the final yield of the varieties. The concept of balanced fertilization is carried out by referring to the creation of a balance of macro-nutrients in the soil so that plants can produce optimally. The research was conducted in a form of experimental study at Tarowang village, Takalar Regency during growing season of 2021 from May to September 2021. A split plot design was used with fertilization package as the main plot and superior varieties as subplots. Three fertilization packages combined inorganic and organic fertilizer were used, namely fertilization package consisted of N: P: K with ratio of 225:100:75, fertilizer package that consisted of N: P: K ratio of 200:100:50 + KNO3 25 kg + Biotani 5cc L-1, and fertilizer package that consisted of N: P: K with a ratio of 200:100:50 + KNO3 25 kg + Ecofarming 5cc L-1. Six superior varieties used were Nasa 29, JH-37, Bisi 2, Bisi 18, SINHAS 1 and NK7328. Based on the level of both factors, 18 treatment combinations were obtained and repeated three times. Responses of maize varieties to fertilization packages, consisted of different combination and dosage of NPK fertilizers, KNO3 and organic fertilizers, were varied between varieties. The treatment of fertilization package of N: P: K = 225:100:75 with Bisi 2 variety gave the highest maize productivity, namely 12.39ton ha-1